Sergio Serulnikov. El poder del disenso. Cultura política urbana y crisis del gobierno español. Chuquisaca 1777-1809. Buenos Aires: Prometeo Libros, 2022, 568 pp. - Salgado Gómez, Mireya (2023)
No presenta resumen